2015
DOI: 10.1126/scisignal.aaa5208
|View full text |Cite
|
Sign up to set email alerts
|

Distinct single-cell signaling characteristics are conferred by the MyD88 and TRIF pathways during TLR4 activation

Abstract: Toll-like receptors (TLRs) recognize specific pathogen-associated molecular patterns and initiate innate immune responses through signaling pathways that depend on the adaptor proteins MyD88 (myeloid differentiation marker 88) or TRIF (TIR domain-containing adaptor protein-inducing interferon-β). TLR4, in particular, uses both adaptor proteins to activate the transcription factor nuclear factor κB (NF-κB); however, the specificity and redundancy of these two pathways remain to be elucidated. We developed a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
154
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(168 citation statements)
references
References 75 publications
9
154
2
Order By: Relevance
“…The loss of MyD88 or TRIF also impaired the induction of LAMP-1 expression following LPS stimulation. The combined role of MyD88 and TRIF in the early induction and sustained activity of NF-κB activity TLR4 signaling (46) suggests that AGS3 may be a NF-κB target gene in macrophages. An involvement of NF-κB in the induction of AGS3 is also consistent with the increase in AGS3 noted in lymphocytes following antigen receptor crosslinking (26).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of MyD88 or TRIF also impaired the induction of LAMP-1 expression following LPS stimulation. The combined role of MyD88 and TRIF in the early induction and sustained activity of NF-κB activity TLR4 signaling (46) suggests that AGS3 may be a NF-κB target gene in macrophages. An involvement of NF-κB in the induction of AGS3 is also consistent with the increase in AGS3 noted in lymphocytes following antigen receptor crosslinking (26).…”
Section: Discussionmentioning
confidence: 99%
“…To explore extrinsic noise sources influencing NF-κB translocation dynamics, Cheng and colleagues measured and modeled FP-RelA nuclear translocation in RAW 264.7 mouse macrophages following lipopolysaccharide (LPS) stimulation. They found that intracellular protein abundance regulated two distinct signaling paths downstream of LPS respectively contributing to variations in initiation timing and duration of NF-κB nuclear localization [30]. …”
Section: Imaging and Fluidics To Measure Nf-κb Pathway Signaling And mentioning
confidence: 99%
“…The fi rst widely used model was developed in 2002 by Hoffmann et al (7), and since then, the Hoffmann group has extensively used a computational systems biology approach to further our understanding of NF-κB dynamics. Their latest study, by Cheng et al (8), describes the distinct signaling characteristics conferred by the MyD88-controlled and TRIF-dependent pathways in the TLR4-stimulated activation of NF-κB.…”
mentioning
confidence: 98%